The Influence Of Influencer Marketing And Price Perception On Iphone Purchase Decisions In Surabaya City - Husen, Ubay; Pudjoprastyono, Hery (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
. Opportunities for telecommunications companies have been greatly enhanced by the development of communications technology, particularly smart phones. Due to their growing functionality, which includes basic communication, internet access, and versatile applications, smart phones are increasingly being used as communication tools. iPhone from Apple Inc. with its unique iOS operating system, has a large market share worldwide. Customers' purchase choices are influenced by variables such as high price and diverse influencer ratings. The purpose of this study is to examine how consumers in Surabaya feel about iPhone prices and the impact of influencer marketing on their purchase choices. A total of 108 respondents, all of whom are iPhone users in Surabaya, were selected using purposive sampling technique for this quantitative research. We used primary and secondary sources to collect data, and we used Partial Least Squares (PLS) to test assumptions, validity, and reliability. The research findings reveal that (1) the use of influencer marketing significantly impacts the choice to purchase an iPhone, and (2) price impression also significantly and positively impacts the decision to purchase.